2011
DOI: 10.2298/avb1106543s
|View full text |Cite
|
Sign up to set email alerts
|

Application of the metabolic profile test in the prediction and diagnosis of fatty liver in Holstein cows

Abstract: The aim of this study was to examine the possibility of using results of metabolic profile test in the prediction and diagnosis of fatty liver in Holstein cows. Forty dry cows, 5 to 7 days before calving, were chosen from the commercial dairy herd and included in the study. Four blood samples were taken by jugular venipuncture from each animal: 5 to 7 days before expected calving (dry period), as well as on day 12, 30 and 60 of lactation. Concentrations of glucose, β-hydroxybutyrate (BHBA), total protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
2
9
1
7
Order By: Relevance
“…In our study, differences in concentrations of the examined variables in jugular vein blood were expected and are in accordance with earlier data (Kida, 2002;Šamanc et al, 2011). Namely, jugular vein insulin concentrations in lactating cows decreased with higher milk production due to the more pronounced NEB during early lactation (Hayirli et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, differences in concentrations of the examined variables in jugular vein blood were expected and are in accordance with earlier data (Kida, 2002;Šamanc et al, 2011). Namely, jugular vein insulin concentrations in lactating cows decreased with higher milk production due to the more pronounced NEB during early lactation (Hayirli et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Chmielewski reported that the contents of NEFA and BHBA were highest in cows characterized by the strongest lipolysis in the first period of lactation (condition BCS > 4). High BCS at calving leads to marked losses in body condition after calving, as well as being associated with fatty liver and increased culling rates . The optimal condition of cows at calving should BCS 3.5.…”
Section: Body Condition Scorementioning
confidence: 99%
“…The metabolic profile is a set of blood haematological, biochemical and enzymatic indicators which provide a more complete evaluation of health status of animals and, if necessary, makes it possible to undertake actions aiming at treating disorders (Kampl et al, 1991;Tornquist and Van Saun, 1999; Mordak and Nicpon, 2006;[amanc et al, 2011).…”
Section: Introductionmentioning
confidence: 99%